2021
DOI: 10.1177/03008916211027627
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy followed by radical surgery in locally advanced vulvar carcinoma: a single-institution experience

Abstract: Background: Squamous cell carcinoma of the vulva is a rare malignancy that affects elderly women. About one-third of vulvar cancers are diagnosed in an advanced stage, requiring extensive surgery. Neoadjuvant chemotherapy (NACT) has been introduced to reduce local tumor burden. In this retrospective study, we analyze the efficacy and toxicity of NACT followed by radical surgery. Methods: Patients with locally advanced vulvar cancer (LAVC) treated at our institution with neoadjuvant platinum and paclitaxel-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As regards the management of locally advanced stages, surgical treatment still remains the pivotal option [ 14 ], despite often requiring large tissue resections, plastic reconstruction, and careful management of severe morbidity [ 15 , 16 , 17 ]. However, some new developments have been introduced as effective possible alternative strategies currently available, including radiation or chemo-radiation, but these suffer from the main limitation of non-repeatability over time, in case of recurrence [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As regards the management of locally advanced stages, surgical treatment still remains the pivotal option [ 14 ], despite often requiring large tissue resections, plastic reconstruction, and careful management of severe morbidity [ 15 , 16 , 17 ]. However, some new developments have been introduced as effective possible alternative strategies currently available, including radiation or chemo-radiation, but these suffer from the main limitation of non-repeatability over time, in case of recurrence [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For chemoradiation, the reported complete response rates are low (50% or less), the 5-year OS is limited to 30-60% [35][36][37][38][39][40], and there is no consistent protocol for the therapy. Moore et al, 1998 [41] analyzed 73 patients with primary, advanced (FIGO III/IV) vulvar cancer and neoadjuvant chemoradiation with cisplatin/5-fluorouracil; 46.5% of the patients had complete remission and 53.3% had a gross residual tumor at the time of surgery, with positive resection margins in 13%.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Marco et al [42 ▪▪ ] reported a retrospective study on 15 LAVC patients treated with NACT followed by surgery. Chemotherapy was platinum-based and consisted of a combination of paclitaxel-ifosfamide-cisplatin, paclitaxel-cisplatin or paclitaxel-carboplatin and was administered in a three-weekly schedule.…”
Section: Current Evidence For Treatment With Neoadjuvant Chemotherapy...mentioning
confidence: 99%
“…Overall response rate was 40–86%. Surgery turned out to be possible in 40–90% of the LAVC patients who received NACT [9,14,42 ▪▪ ,43 ▪▪ ,44–47].…”
Section: Current Evidence For Treatment With Neoadjuvant Chemotherapy...mentioning
confidence: 99%